Advancements in photodynamic therapy of esophageal cancer - Bartusik-Aebisher, Dorota; Osuchowski, Michał; Adamczyk, Marta; Stopa, Joanna; Cieślar, Grzegorz; Kawczyk-Krupka, Aleksandra; Aebisher, David (Frontiers in Oncology, 2022)
: Poor prognosis of patients with esophageal cancer leads to constant search for new ways of treatment of this disease. One of the methods used in high grade dysplasia, superficial invasive carcinoma and sometimes as palliative care is photodynamic therapy (PDT). This method has come a long way from the first experimental studies to registration in the treatment of esophageal cancer and is constantly being improved and refined. In this review, the authors searched through the available literature, analyzed the available photosensitizers, methods of carrying out the procedure, the effects of PDT treatment and concepts for future development. This review describes esophageal cancer, current treatment methods, the introduction to PDT, the photosensitizers (PS) used in esophageal carcinoma PDT, PDT in squamous cell carcinoma (SCC) of the esophagus and PDT in invasive adenocarcinoma of esophagus. For this review, research and review articles from PubMed and Web of Science databases were used. The key words used were: “photodynamic therapy in esophageal cancer” during the years 2000–2020. The total number of papers returned was 1000. After dividing the review into topic blocks and analyzing the searched publications, 117 articles were selected.